Monilethrix with Variable Expressivity - Bindurani, S (Medknow Publications & Media Pvt Ltd, 2013)
Monilethrix is a rare autosomal dominant hair shaft disorder with variable expressivity. It usually presents with short broken scalp hairs and follicular hyperkeratosis. Light microscopy of hair reveals a beaded appearance. Here, we report the case of a 32-year-old male who presented with sparse hair and follicular keratotic papules in the absence of any family history.